Analisis Pertumbuhan Gigi Molar Susu pada Anak Stunting Ditinjau dari Status Gizi - Nengsih, Cicih; Praptiwi, Yenni Hendriani; Laut, Deru Marah; Nurjanah, Neneng; Handayani, Ratna Dwi (Poltekkes Kemenkes Bandung, 2025)
Tooth eruption is a part of dental growth and development characterized by the movement of teeth toward the oral cavity following crown formation. This process is influenced by various factors, including nutritional status, which plays an important role in dental growth and the timing of tooth eruption. This study aimed to determine the relationship between the nutritional status of stunted children and the growth of milk molar teeth at the UPTD Aren Jaya Health Center. The research used was an analysis with a cross-sectional approach, a population of 58 stunted children at the UPTD Aren Jaya Health Center, with sampling using total sampling. Data analysis using statistical tests with the Spearman Rank correlation test. The results of the study showed that the nutritional status of stunted children at UPTD Aren Jaya Health Center was mostly within normal criteria, with a percentage of 97.2%. The growth of milk molar teeth in stunted children at UPTD Aren Jaya Health Center, all children had erupted by 100%. The results of this study can be concluded that there was no relationship between the nutritional status of stunted children and the growth of milk molar teeth at UPTD Aren Jaya Health Center. It is recommended for the health center to pay attention by conducting counseling to parents, this is done so as not to increase the population of stunted toddlers at the Aren Jaya Health Center UPTD.